Myeloperoxidase aggravates pulmonary arterial hypertension by activation of vascular Rho-kinase - Klinke, Anna; Berghausen, Eva; Friedrichs, Kai; Molz, Simon; Lau, Denise; Remane, Lisa; Berlin, Matthias; Kaltwasser, Charlotte; Adam, Matti; Mehrkens, Dennis; Mollenhauer, Martin; Manchanda, Kashish; et al. (JCI insight, 2018)
Pulmonary arterial hypertension (PAH) remains a disease with limited therapeutic options and dismal prognosis. Despite its etiologic heterogeneity, the underlying unifying pathophysiology is characterized by increased vascular tone and adverse remodeling of the pulmonary circulation. Myeloperoxidase (MPO), an enzyme abundantly expressed in neutrophils, has potent vasoconstrictive and profibrotic properties, thus qualifying as a potential contributor to this disease. Here, we sought to investigate whether MPO is causally linked to the pathophysiology of PAH. Investigation of 2 independent clinical cohorts revealed that MPO plasma levels were elevated in subjects with PAH and predicted adverse outcome. Experimental analyses showed that, upon hypoxia, right ventricular pressure was less increased in Mpo-/- than in WT mice. The hypoxia-induced activation of the Rho-kinase pathway, a critical subcellular signaling pathway yielding vasoconstriction and structural vascular remodeling, was blunted in Mpo-/- mice. Mice subjected to i.v. infusion of MPO revealed activation of Rho-kinase and increased right ventricular pressure, which was prevented by coinfusion of the Rho-kinase inhibitor Y-27632. In the Sugen5416/hypoxia rat model, PAH was attenuated by the MPO inhibitor AZM198. The current data demonstrate a tight mechanistic link between MPO, the activation of Rho-kinase, and adverse pulmonary vascular function, thus pointing toward a potentially novel avenue of treatment.
Keywords: Peroxidase; kinázy asociované s rho; remodelace cév; rho-Associated Kinases; Humans; lidé středního věku; kohortové studie; Female; dospělí; Lung; krysa rodu Rattus; peroxidasa; Amides; lidé; Hypoxia; Recombinant Proteins; zvířata; Hypertension, Pulmonary; myši; plíce; Pyridines; myši inbrední C57BL; vazokonstrikce; amidy; Mice; hypoxie; myši knockoutované; Cohort Studies; Adult; rekombinantní proteiny; plicní hypertenze; potkani Sprague-Dawley; ženské pohlaví; Kaplanův-Meierův odhad; Male; Mice, Knockout; Middle Aged; Vascular Remodeling; Mice, Inbred C57BL; Infusions, Intravenous; pyridiny; Rats; Kaplan-Meier Estimate; Rats, Sprague-Dawley; Animals; arteria pulmonalis; mužské pohlaví; Vasoconstriction; Disease Models, Animal; intravenózní infuze; Pulmonary Artery; modely nemocí na zvířatech